A legislação ambiental e seus efeitos no controle dos danos ambientais e na recomposição de áreas legalmente protegidas: uma análise no período de 1987 – 2018 para a região central do estado de São Paulo (Brasil) - Andrade, Valéria Aparecida David (2019)
Several laws, at national and state scope, have been instituted for environmental assessment aiming at reducing the damage resulting from the replacement of native vegetation by anthropic agricultural and non-agricultural areas, as well as the obligation to recompose deforested areas. This study analyzed the effectiveness of the legislation and environmental inspection of the State São Paulo in relation to the assessment, prevention and recovery of environmental damage, within the territorial boundaries of 23 municipalities of the Central Region of the State São Paulo, based in a quantitative inventory of the Environmental Infringement Registration (EIRs) and Environmental Recovery Commitment Terms (ERCTs), drafted over the 31-year period (1987-2018). A total of 1,863 EIRs and, respectively, 1,207 signed ERCTs were quantified, with 61% of EIRs related to legally protected areas categorized as Permanent Preservation Areas. In the period from 2008 to 2018, a total assessment area equivalent to 1,753.05 ha was estimated, of which 1,107.71 ha covered with native vegetation; 65.92 ha sent for regularization via environmental licensing, and 664.53 ha related to native vegetation recovery procedures based on signed ERCTs. The municipalities considered potentially susceptible or critically compromised due to the higher values of EIRs and assessment areas (ha) were, respectively, São Carlos (188; 490.31 ha), Ibitinga (90; 301.62 ha), and Araraquara (85; 100.44 ha), over the 10 year period (2008 - 2018). In a potentially susceptible opposite situation, the municipalities of Bocaina (2; 0.18 ha), Águas de São Pedro (4; 0.68 ha), and Nova Europa (2; 0.99 ha) were identified. The increase in Gross Domestic Product values, and the change in land use related to increases in agricultural anthropic area and native vegetation area were pressure vectors directly related to the number of EIRs registrations, over the 31-year period (1987-2018). The number of environmental enforcement agencies in the study area did not directly influence the number of EIA registrations.The results obtained highlight the effectiveness of environmental legislation in its satisfactory regulatory capacity, with reference to what is real and true, with concern to the EIRs and ERCTs quantifying, within the territorial boundaries of the 23 municipalities of the Central Region of the state of São Paulo, over the 31 year period (1987-2018). It also indicates that the improvement of environmental inspection procedures inhibits the occurrence of new damage, as an essential tool for the effective control of deforestation and the recovery of environmentally degraded areas.